علم الجرح و التعدیل کا تعارف اور مراتب ِجرح و تعدیل: ایک تحقیقی مطالعہ: Introduction to the Science of Jarh and Ta'dil and the Levels of Jarh and Ta'dil: A Research Study - Shamim Akhtar; Muhammad Saad Dehlvi (International Research Journal of Arabic and Islamic Studies, 2024)
The science of Jarh and Ta'dil is fundamental in the field of Hadith studies, focusing on the evaluation and authentication of narrators. This discipline ensures the reliability of hadith by scrutinizing the character and trustworthiness of the individuals transmitting them. The article introduces the principles and methodologies of Jarh and Ta'dil, outlining its historical development and significance in Islamic scholarship. It also delves into the different levels of criticism (Jarh) and commendation (Ta'dil) applied to narrators, explaining the criteria and terminologies used by scholars. By understanding these gradations, one can appreciate t he meticulous efforts of early scholars in preserving the integrity of hadith literature. This research study aims to elucidate the complexities and importance of Jarh and Ta'dil in the authentication process of Islamic traditions.